Delmira Agustini: Narrations of Life and Death (2020)
Delmira Agustini (1886-1914) had already published three books of poetry and had won the recognition of critics and the public when she was murdered in July 6, 1914 by who had been her husband. This event, which has had a prominent place in the Uruguayan police chronicle and in the literary history, was narrated by biographies and fictions for more than a century. This story has been told with some variants that have been reiterated a knot of conflicts around some protagonists: Delmira, her mother, her boyfriend-husband-lover-murderer, and Manuel Ugarte as the impossible lover. However, the reading of the manuscripts indicates the relevance of the figure of his father: Santiago Agustini, almost an unmentioned shadow in the stories about this "tragedy". This work tries to raise the importance of this relationship to understand the poetic production of Agustini and to open, from that perspective, the plot of this emotional and intellectual relationships that fed the author’s life and poetry.